Physiological changes and recovery after short-term high-altitude hypoxia: a narrative review - Fathiah Jabir; Rosnah Ismail; Mohd Hasni Jaafar (Universiti Kebangsaan Malaysia, 2025)
Exposure to high altitude induces substantial physiological changes across various systems, enabling humans to withstand hypoxic environments. These physiological changes have been frequently explored and described in the existing literature. In contrast, the process of readjusting to lower altitudes, known as high-altitude de-acclimatisation, remains understudied, especially for individuals who spend brief periods at high altitudes. This narrative review aims to consolidate existing research on the physiological alterations and recovery patterns experienced by individuals returning from short-term stays at high altitudes, highlighting the acclimatisation and de-acclimatisation processes. A total of 29 articles were reviewed to extract insights from current evidence. The findings reveal that de-acclimatisation is a complex process influenced by various factors. Cardiovascular adaptations, such as increased heart rate, cardiac output, and pulmonary artery pressure, begin to reverse upon descent but demonstrate varying recovery timelines. While heart rate typically normalises within days, stroke volume and pulmonary pressures may take weeks to months to recover fully. Similarly, respiratory adaptations, including ventilatory drive and oxygen saturation, show gradual improvement, although symptoms such as nocturnal hypoxemia and periodic breathing may persist for several days’ post-descent. Haematological parameters, such as haemoglobin and haematocrit levels, decline rapidly, yet full recovery of molecular and systemic markers may extend beyond three months. Metabolic and immune system changes, including increased oxidative stress and immune suppression persist, highlighting the long-term impact of high-altitude exposure. Hormonal fluctuations affecting reproductive health in both sexes further underscore the systemic effects of high-altitude environments. This review also highlights the need for comprehensive public health strategies, including medical consultations prior to travel to high altitude, plans for structured acclimatisation and de-acclimatisation protocols, and extended monitoring for vulnerable populations such as frequent high-altitude workers or hikers with pre-existing medical conditions. Although progress has been made in understanding the physiological challenges of de-acclimatisation, substantial gaps remain, particularly in the long-term implications and recovery trajectories. Addressing these gaps through targeted research will enhance guidelines for managing high-altitude transitions and safeguarding the health of diverse populations.